2022
DOI: 10.1038/s41598-022-07984-w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the impact of COVID-19 in France on cancer care: a differentiated impact

Abstract: The COVID-19 pandemic has had a substantial and lasting impact on care provision, particularly in the field of cancer care. National steering has helped monitor the health situation and adapt the provision and organisation of care. Based on data from the French administrative healthcare database (SNDS) on the entire French population (67 million people), screening, diagnostic and therapeutic activity was monitored and compared 2019 on a monthly basis. A noteworthy decline in all activities (with the exception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…A subtotal of 41 [ 14 , 15 , 20 , 21 , 29 , 30 , [32] , [33] , [34] , 37 , 40 , 42 , 44 , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] and 12 [ 20 , 21 , 42 , 65 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] studies reported diagnosis, and breast imaging outcomes, respectively. Key results from the individual studies are summarised narratively below, and presented in more detail in Table 2 and AppxTable F.6-F.8 ( Appendix F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subtotal of 41 [ 14 , 15 , 20 , 21 , 29 , 30 , [32] , [33] , [34] , 37 , 40 , 42 , 44 , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] and 12 [ 20 , 21 , 42 , 65 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] studies reported diagnosis, and breast imaging outcomes, respectively. Key results from the individual studies are summarised narratively below, and presented in more detail in Table 2 and AppxTable F.6-F.8 ( Appendix F ).…”
Section: Resultsmentioning
confidence: 99%
“…In medical imaging studies or studies with a mixed screening and symptomatic population (AppxTable F.8a), the number of mammography examinations during the pandemic [ 20 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] ] generally showed a relative reduction of between 8.9% [ 84 ] and 92.7% [ 81 ], with 67% (6/9) of studies reporting cumulative (or average) reductions of 9%–37% [ 20 , [77] , [78] , [79] , 82 , 83 ]. In an additional 6 studies of symptomatic populations (AppxTable F.8b) [ 20 , 21 , 29 , 37 , 42 , 73 ], a similar reduction was found for the number of diagnostic mammography (range: 4.7%–83.8%) with half of the studies observing reductions between 4% and 21% [ 20 , 29 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in cancer screening were reported for cervical cancer (−7.5 to −90%) in Canada, the United States, Brazil, France, Taiwan, Belgium, and 17 selected low- and middle-income countries (LMICs) [ 19 ▪ , 21 ▪ 23 ▪ , 30 ▪▪ , 33 , 35 ▪ , 36 , 38 – 40 , 43 , 46 ]. A significant drop in digestive endoscopies (−19 to −29%) was reported in Lithuania and France [ 17 , 39 ]. Reductions in colon cancer screening (−8.1 to −95%) were registered in Canada, the United States, France, Belgium, Qatar, and 17 selected LMICs [ 14 , 15 , 16 ▪ , 23 ▪ , 25 , 30 ▪▪ , 33 , 35 ▪ , 36 39 , 43 , 44 ].…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%
“…A significant drop in digestive endoscopies (−19 to −29%) was reported in Lithuania and France [ 17 , 39 ]. Reductions in colon cancer screening (−8.1 to −95%) were registered in Canada, the United States, France, Belgium, Qatar, and 17 selected LMICs [ 14 , 15 , 16 ▪ , 23 ▪ , 25 , 30 ▪▪ , 33 , 35 ▪ , 36 39 , 43 , 44 ]. LCS rates fell in Canada, the United States, Ireland, and 17 selected LMICs (−21 to −44.6%) [ 11 , 24 , 30 ▪▪ ].…”
Section: Covid-19 and Cancer Screening Programmentioning
confidence: 99%
“…The implementation of this strategy has become a significant challenge in the era of the coronavirus disease 2019 (COVID-19) pandemic. Impeded access to health care services, supply chain disruptions, and deteriorations in the financial health of countries are all factors that have undermined the implementation of CC-prevention measures [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%